Microbiological quality assessment of herbal medicinal products and antibiotic resistance profile of bacteria - Shorifujjaman, Md; Kabir, Md Shahinur (Bangladesh Journal of Botany, 2019)
The microbiological quality of some herbal medicinal products available in Dhaka, Bangladesh was evaluated. In the studied samples, the total aerobic bacterial count (TABC) varied from 6.20 × 102 to 2.97 × 105 cfu /ml, total yeast and mold count ranged from 0 to 1.80 × 104 cfu /ml, total coliform count varied from 0 to 2.80×103 cfu/ml and total staphylococcal count (TSC) ranged from 0 to 2.30 × 104 cfu/ml. A strong positive correlation (r = 0.849) was observed between TABC and TSC. Out of 24 herbal medicinal samples examined, 5 (20.83%) did not comply with the microbiological criteria set by internationally recognized organizations. The study revealed that 100% of the Escherichia coli isolates were resistant to amoxicillin and penicillin G, 85.71% were resistant to nitrofurantoin and 71.43% were resistant to ceftriaxone and cefuroxime: and 57.14% were resistant to erythromycin. Among the Staphylococcus aureus isolates tested, 100% were resistant to amoxicillin, nalidixic acid and Penicillin G; whereas 33.33% showed resistance to cefuroxime.